A SERVQUAL approach to identifying the influences of service quality on leasing market segment in the German financial sector. Issue 6 (6th August 2018) - Ramanathan, Usha; Win, Sandar; Wien, Andreas
Abstract : Purpose: The purpose of this paper is to determine the nature of the relationship between service quality and desired customer behaviours in the leasing market using an appropriate service quality measurement model. The authors take a step further by recognising the possible differences in influence of service quality in private and corporate customers, and those business dealings with low, medium and high lease values. Design/methodology/approach: The authors use deduction method to test the SERVQUAL in the German leasing market and the relationship between customer satisfaction and desired behavioural outcomes. The developed questionnaire is based on the 22-item scale of the SERVQUAL approach. Samples are selected based on convenience sampling. Findings: The authors found differences in the levels of influence by SERVQUAL dimensions on corporate and private customers as well as among those customers with different leasing contract values. From the regression analyses, it is clear that "assurance" from the leasing company is the most common SERVQUAL dimension that has significant impact on overall service quality perceptions and obtaining customers satisfaction and loyalty (behavioural outcomes). Originality/value: The authors recognised that all financial services are not created equally to meet customer demands. Hence, the customer expectations of service quality from these services will be different. The authors contributed to the marketing literature by studying customer perceptions of service quality by specifying financing aspects of financial services, i.e. leasing. The authors further contributed to the literature of SERVQUAL model in financial services by dividing customers into two different types of customers and those with diverse leasing contract values. The authors found that priorities given on service quality dimensions by them are different. These concepts were never considered in the literature. This also implies that future studies on financial services marketing need to recognise such differences in the research.